2022
DOI: 10.1111/nejo.12384
|View full text |Cite
|
Sign up to set email alerts
|

Confirming the Impact of Training on Negotiators and Organizations

Abstract: This study seeks to determine the long-term impacts of training on negotiators and organizations. Although previous studies have linked training to negotiation outcomes, their findings have been basedprimarily on experimental data. This article analyzes survey data from business students who received negotiation training from the author over a period of ten years and were employed at the time of the survey. The survey sought to determine if respondents applied the skills learned in negotiation classes to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Similarly, Lopez-Lemus (2019) argue SMEs businesspeople and entrepreneurs must apply suitable management strategies in order to gain expertise and skills to run their business. Other studies report that negotiation skills explicit training is both feasible and necessary for organizations success and internationalization (Baber, 2022 Paul, 2020). With regard to manager's age, it has been demonstrated that this variable does not affect the performance of medium-sized companies in Peru; however, it should be noted that the age ranges patterns reported here differ from other studies (Besar et al, 2017;Costin, 2012;Katsaros et al, 2014).…”
Section: Mean Extracted Variancecontrasting
confidence: 69%
See 1 more Smart Citation
“…Similarly, Lopez-Lemus (2019) argue SMEs businesspeople and entrepreneurs must apply suitable management strategies in order to gain expertise and skills to run their business. Other studies report that negotiation skills explicit training is both feasible and necessary for organizations success and internationalization (Baber, 2022 Paul, 2020). With regard to manager's age, it has been demonstrated that this variable does not affect the performance of medium-sized companies in Peru; however, it should be noted that the age ranges patterns reported here differ from other studies (Besar et al, 2017;Costin, 2012;Katsaros et al, 2014).…”
Section: Mean Extracted Variancecontrasting
confidence: 69%
“…Karadag (2017) affirmed manager's level of education influences the performance of a medium-sized firm, while other studies suggest the opposite (Besar et al, 2017;Hambrick & Mason, 1984). Additionally, managers are expected to demonstrate effective negotiation skills (Baber, 2022;Letonja et al, 2016). Since the studies' reported results exploring the analysis of manager characteristics and medium-sized firm performance are inconclusive and considering that Peru, which is in a category of a developing country (Pawlak & Kołodziejczak, 2020;Rojas-Berrio et al, 2022), has not been analyzed in those studies, there seems to be an opportunity to study these variables in a different scenario.…”
Section: Introductionmentioning
confidence: 97%
“…It also demonstrates a willingness to be reasonable and acknowledge the legitimacy of the other side's position. Skilled negotiators often reserve a small final concession they can make at the end to make the agreement more reasonable and try to encourage an agreement in their favor rather than one party over the other [6]. At the same time, in the negotiation, both sides should constantly adjust their behavior and attitude, make necessary concessions, and understand the requirements of the other side, so that the negotiation may be successful and finally reach a satisfactory agreement for both sides.…”
Section: Main Research 21 Challenge About Negotiationmentioning
confidence: 99%
“…By using the "focus first" strategy, graduates can avoid wasting time and energy on problem-solving. Graduates often face complex information, distracting people from more important matters [6]. Therefore, graduates need always to keep their minds sharp and clear, not to be confused by appearances, and avoid making decisions in a panic and on impulse.…”
Section: Interest-based Negotiationmentioning
confidence: 99%